2023
DOI: 10.1371/journal.pone.0285771
|View full text |Cite
|
Sign up to set email alerts
|

Association between cancer stigma and cervical cancer screening uptake among women of Dhulikhel and Banepa, Nepal

Abstract: Background Cervical cancer ranks as the most common cancer among Nepalese women with a high incidence and mortality. Despite evidence that effective screening programs reduce disease burden, screening services are under-utilized. Cancer stigma can be a major barrier to cervical cancer screening uptake among Nepalese women. Objectives This study assessed the association between cancer stigma and cervical cancer screening uptake among women residing in semi-urban areas of Kavrepalanchok district (Dhulikhel and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“… 51 Despite growing awareness of gynecologic cancer, perceptions of discrimination might still be widespread. 52 Secondly, the findings suggest that gynecologic cancer patients who struggled with stigmatized beliefs are under significant stress due to sensitivities related to their cancer diagnosis and experience, consistent with previous results in other populations. 53 Studies of stigma among individuals with chronic health conditions have shown that they experienced significant social isolation, anxiety and stress as a result of internalized negative beliefs about their health conditions.…”
Section: Discussionsupporting
confidence: 88%
“… 51 Despite growing awareness of gynecologic cancer, perceptions of discrimination might still be widespread. 52 Secondly, the findings suggest that gynecologic cancer patients who struggled with stigmatized beliefs are under significant stress due to sensitivities related to their cancer diagnosis and experience, consistent with previous results in other populations. 53 Studies of stigma among individuals with chronic health conditions have shown that they experienced significant social isolation, anxiety and stress as a result of internalized negative beliefs about their health conditions.…”
Section: Discussionsupporting
confidence: 88%
“…Despite being one of the most preventable and treatable forms of cancer, it continues to be a major cause of women killing 11 in 100000 women in developing countries after breast cancer [ 4 ]. In Nepal, cervical cancer is the most common cancer, with 1,493 annual deaths in 2020 [ 5 ]. The Government of Nepal (GoN) developed national guidelines for Cervical Cancer Screening and Prevention (CCSP) in 2010 with the goal of screening at least 50% of the target population (women aged 30–60 years).…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Stigma with a diagnosis of cancer is a major issue in certain societies in LMICs where cancer is often perceived as a life-threatening event, evoking feelings of uncertainty, fear, and loss in individuals, irrespective of their prognosis. 3 , 4 These emotional responses contribute to the stigma surrounding the disease. Specifically for women, it also uncovers the underlying lack of agency embedded in patriarchal societies where they have fewer basic rights to education and health, choice of partner, determining a family, mobility, and labor participation.…”
mentioning
confidence: 99%